THE IMPACT OF LONG TERM RELATIONSHIP, PROCESS INTEGRATION, COOPERATION ON SUPPLY CHAIN MANAGEMENT PERFORMANCE AND COMPETITIVE ADVANTAGE - AFRILIYANI, UCI; SUNARKO, BAMBANG (INDONESIAN RESEARCH SOCIETY, 2019)
This research is conducted on Small and Medium Industries of Gumelem Coconut Sugarlocated in Gumelem, Susukan Subdistrict, Banjarnegara Regency. This study takes the title: